Educação em Saúde no território brasileiro no período técnico-científico-informacional - Costa, Soneide Moura da (2021)
Health Education is a process of professional training for the purpose of a continuous and updated practice of care in the service. In Brazil at the technical-scientific-informational period, this process has been made possible through Information and Communication Technologies (ICTs), including the Virtual Learning Environment of the Brazilian Unified Health System (AVASUS) as an example. In this context, the general objective of the research was to analyze the Health Education process in the Brazilian territory considering the technical-scientific-informational period. Based on this central idea, the following specific objectives were listed: to highlight the normative trajectory of Health Education in Brazil; to analyze the Continuing Health Education (CHE) in the context of ICTs; to describe the configuration of the Brazilian territory in the light of socioeconomic and health care indicators; and to evaluate the impacts of the training offered by AVASUS on the Health service in Brazil. The methodological procedures included bibliographic research on Health Education, CHE, technical-scientific-informational period, territory, informatization of the territory, internet, technique, network, ICT and Virtual Learning Environment (VLE). Documentary research was also used in sources such as: reports from national health conferences; decrees, ordinances and websites of the Ministry of Health, Brazilian Institute of Geography and Statistics (IBGE), Institute of Applied Economic Research (Ipea), Department of Informatics of the Unified Health System (DATASUS), telegeography portal; and AVASUS platform. In 2018, was carried out the application an online questionnaire available on that platform, aiming to assess the impacts of the formation of AVASUS in the Health Service in Brazil. The results indicated that Health Education in Brazil had its trajectory outlined in national conferences on the topic, which discussions contributed to the elaboration of the National Policy on Continuing Health Education (PNEPS), among others. In the technical-scientific informational period, Health Education promoted by PNEPS, expands its possibilities of operationalization through ICTs and the training made possible by AVASUS is an example. Despite the socioeconomic and healthcare heterogeneity of Brazil, the training offered through this platform covers the entire national territory.